Factors Associated with Blood Glucose Levels in Neonates at Aura Syifa Hospital - Kartika Dyah Bestari; Sumy Dwi Antono; Susanti Pratamaningtyas; Dwi Estuning Rahayu (Akademi Keperawatan Yarsi Samarinda, 2026)
In the neonatal period, hypoglycemia is the most common metabolic disorder that carries a risk of long-term neurological impairment. The purpose of this study was to analyze factors associated with blood glucose levels in neonates at Aura Syifa Hospital, including maternal obesity, history of gestational diabetes mellitus, maternal age ≥35 years, and neonatal hypothermia. This study was an observational analytic study with a retrospective case-control design using 36 respondents (18 cases, 18 controls) through purposive sampling technique. Univariate analysis and bivariate analysis with Chi-Square and Fisher's Exact Test were applied. Maternal obesity was found in the majority of respondents at 58.3%, hypothermia was experienced by most neonates at 63.9%, and blood glucose distribution showed equal proportions of hypoglycemia and normal at 50% each. Based on the statistical test results, there was no significant relationship between maternal obesity (p = 0.310; OR = 2.000) and maternal age ≥35 years (p = 0.298; OR = 0.481) with neonatal blood glucose levels. There was a significant relationship between history of gestational diabetes mellitus (p = 0.001; OR = 21.250) and hypothermia (p = 0.000; OR = 4.600) with neonatal blood glucose levels. Mothers who experienced gestational diabetes mellitus during pregnancy is the most dominant factor associated with neonatal blood glucose levels, followed by hypothermia. It is expected that healthcare providers will optimize blood glucose screening in neonates born to at-risk mothers and consistently implement hypothermia prevention measures from the time of delivery